Assessment of prescribing, dispensing, and patient use pattern of antihypertensive drugs for patients attending outpatient department of Hiwot Fana Specialized University Hospital, Harar, Eastern Ethiopia - Shukrala F; Gabriel T (Dove Medical Press, 2015)
Fedila Shukrala,1 Tesfaye Gabriel2 1Dil Chora Referral Hospital, Dire Dawa, Ethiopia; 2Department of Pharmaceutics and Social Pharmacy, School of Pharmacy, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia Background: Hypertension is a global concern and is one of the key preventable risk factors for cardiovascular events, resulting in unnecessary morbidity and mortality. The aim of this study was to assess the prescribing, dispensing and patient use pattern of antihypertensive drugs among patients attending Hiwot Fana Specialized University Hospital outpatient department.Methods: A hospital-based cross-sectional study was conducted in Hiwot Fana Specialized University Hospital on assessment of the prescribing, dispensing, and patient use pattern of antihypertensive drugs among patients who were above the age of 18 years and attending outpatient department from April 1–May 31, 2013. Data collection was conducted by reviewing the record of patients and direct observation of the dispensing process of randomly selected patients to measure average dispensing time, and direct interview with the patients. Results: A total of 400 patients met the inclusion criteria; out of the 400 patients studied, 63.5% were females. Most of the patients had Stage 1 hypertension (69%), followed by Stage 2 hypertension (31%). Out of the total number of patients, 264 were with different comorbid conditions: diabetes mellitus (64.3%), followed by congestive heart failure (15.1%) and ischemic heart disease (2.3%). The most frequently prescribed class of antihypertensive drugs was diuretics, of which hydrochlorothiazide was the most frequently prescribed drug, both in single (55%), followed by enalapril (22.3%), methyl dopa (11.2%), atenolol (6.9%), and nifedipine (4.6%), and in combination with other antihypertensive drugs. The average dispensing time was 1.2 minutes, and 75% of the patients left the counter with inadequate information about the dosage.Conclusion: All antihypertensive drugs prescribed were in compliance with the Ethiopian Standard Treatment Guidelines. This study showed that most outpatients with hypertension in our hospital received monotherapy. Diuretics and angiotensin converting enzyme inhibitors were the most frequently prescribed classes of antihypertensive drugs in both monotherapy and combination therapy. Keywords: hypertension, antihypertensive drugs, monotherapy, combination therapy, fixed dose combination, compliance